Measurement and evaluation in the elementary school - Greene, Harry A.; Albert N. Jorgensen;Gerberich, J. Raymond (New York : Longmans Green and Co., 1958)
This book is designed especially for the use of elementary-school teachers and students of elementary education.
Chapter1. Measurement, Evaluation and the Classroom Teacher -- Chapter2. Development of Educational and Mental Measurement -- Chapter3. Educational and Mental Measuring Instrument and Techniques -- Chapter4. Essential Qualities of a Good Measuring Instrument -- Chapter5. Constructing and Using Standardized Tests -- Chapter6. Constructing and Using Oral and Essay Tests -- Chapter7. Constructing and Using Informal Objective Test -- Chapter8. Constructing and Using Performances Tests -- Chapter9. Constructing and Using Evaluation Tools and Techniques -- Chapter10. Using Intelligence and Aptitude Tests -- Chapter11.Using Personality Instruments and Techniques -- Chapter12. Summarizing the Results of Measurement -- Chapter13. Interpreting the Results of Measurement -- Chapter14. Determining Relationships Among The Result of Measurement -- Chapter15. Measuring and Evaluating in the Receptive Language Arts ..
Includes index.
Keywords: EDUCATION -- ELEMENTARY SCHOOL